(3GdTeGFd GdfHhjI hGdNUGd GdeUWahjIs - (3eMeO Hf YjSi Hf ShQI Hf ehSi GdSdej GdHhZj GdJQePj, CHh YjSi ,J (B279 (3g` s ((3eMeO Hf YHO GdMdje GdefjQi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd GdTjN GdMGaX CHh YjSi eMeO Hf YjSi Hf ShQg GdJQePi QMeg Gddg (B: (3HGH eG LGA ai Ndb QShd Gddg Udi Gddg Ydjg hSde MOKfG CHh QLG bJjHI Hf SYjO s
(3BNQgG (B:s
(3MOKfG GHf Yha Yf GHf SjQjf bGd (B: (3gPG GdMOjK Ojf aGfXQhG eef JCNPhf Ojfce s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1059s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs